Synthesis and Biological Evaluation of 2-Hydroxy-3-[(2-aryloxyethyl)amino]propyl 4-[(Alkoxycarbonyl)amino]benzoates - Jan Tengler; Iva Kapustíková; Matúš Peško; Rodney Govender; Stanislava Keltošová; Petr Mokrý; Peter Kollár; Jim O'Mahony; Aidan Coffey; Katarína Král'ová; Josef Jampílek (The Scientific World Journal)
A series of twenty substituted 2-hydroxy-3-[(2-aryloxyethyl)amino]propyl 4-[(alkoxycarbonyl)amino]benzoates were prepared and characterized. As similar compounds have been described as potential antimycobacterials, primary in vitro screening of the synthesized carbamates was also performed against two mycobacterial species. 2-Hydroxy-3-[2-(2,6-dimethoxyphenoxy)ethylamino]-propyl 4-(butoxycarbonylamino)benzoate hydrochloride, 2-hydroxy-3-[2-(4-methoxyphenoxy)ethylamino]-propyl 4-(butoxycarbonylamino)benzoate hydrochloride, and 2-hydroxy-3-[2-(2-methoxyphenoxy)ethylamino]-propyl 4-(butoxycarbonylamino)benzoate hydrochloride showed higher activity against M. avium subsp. paratuberculosis and M. intracellulare than the standards ciprofloxacin, isoniazid, or pyrazinamide. Cytotoxicity assay of effective compounds was performed using the human monocytic leukaemia THP-1 cell line. Compounds with predicted amphiphilic properties were also tested for their effects on the rate of photosynthetic electron transport (PET) in spinach (Spinacia oleracea L.) chloroplasts. All butyl derivatives significantly stimulated the rate of PET, indicating that the compounds can induce conformational changes in thylakoid membranes resulting in an increase of their permeability and so causing uncoupling of phosphorylation from electron transport.